Identifying and managing care for children with autism spectrum disorders in general practice: A systematic review and narrative synthesis. (15th July 2020) - Coughlan, Barry; Duschinsky, Robbie; O'Connor, Mary‐Ellen; Woolgar, Matt
Abstract: Many healthcare systems are organised such that General Practitioners (GPs) often have a key role in identifying autism spectrum disorders (hereafter collectively referred to as autism) in children. In this review, we explored what GPs know about autism and the factors that influence their ability to identify and manage care for their patients with autism in practice. We conducted a systematic narrative review using eight electronic databases. These included Embase and MEDLINE via Ovid, Web of Knowledge, PsycINFO via Ebscohost, PubMed, Scopus, ProQuest Dissertations and Thesis, and Applied Social Sciences Index and Abstracts (ASSIA) via ProQuest. Our search yielded 2, 743 citations. Primary research studies were included, and we did not impose any geographical, language or date restrictions. We identified 17 studies that met our inclusion criteria. Studies included in the review were conducted between 2003 and 2019. We thematically synthesised the material and identified the following themes: the prototypical image of a child with autism; experience, sources of information, and managing care; barriers to identification; strategies to aid in identification; and characteristics that facilitate expertise . Together, the findings from this review present a mixed picture of GP knowledge and experiences in identifying autism and managing care for children with the condition. At one end of the continuum, there were GPs who had not heard of autism or endorsed outmoded aetiological theories. Others, however, demonstrated a sound knowledge of the conditions but had limited confidence in their ability to identify the condition. Many GPs and researchers alike called for more training and this might be effective. However, framing the problem as one of a lack of training risks silences the array of organisational factors that impact on a GP's ability to provide care for these patients.